The World Bank's Market Assisted Land Reform in South Africa and Brazil (1994-2002) - Mendes Pereira, Joao Marcio [UNESP] (Pontificia Universidade Catolica Do Rio Grande Sul, 2017)
The paper analyzes the World Bank's market-assisted land reform (MALR), addressing its rationality, the political agenda to which it belonged and the results of its implementation in South Africa and Brazil. After identifying it as part of the broader process of updating the neoliberal agenda articulated in the mid-1990s, the article discusses the World Bank's agrarian program and details its components, including the MALR. It then summarizes both the criticism of the Bank to redistributive agrarian reforms of the past, based on land expropriation by the state, as well as the supposed advantages of MALR. It also discusses the political intentions that guided its implementation and analyzes the socio-economic and political results of MALR in both countries.
Keywords: World Bank; agrarian reform; land market; neoliberalism; rural poverty